The Influence of Attitudes, Internal Locus, and Financial Socialization Agents on Financial Management Behavior - Tsuroyya, Kharisma; Nuryana, Ita (Economic Education Analysis Journal, 2021)
This study aims to analyze the influence of financial attitudes, internal control locus, and financial socialization agents on student financial management behavior. The population in this study were students of the Economic Education Department of Universitas Negeri Semarang 2018 class of 346 students. The sample used was 186 students using proportional random sampling technique, with sampling using the Slovin formula. Data were collected using a questionnaire. The analytical method used is descriptive statistical analysis and Structural Equation Modeling - Partial Least Square (SEM-PLS) analysis using WarpPLS 6.0 software. The results showed that financial attitudes had a positive and significant effect on financial management behavior. The locus of internal control has a positive and significant effect on financial management behavior. Financial socialization agents have a positive and significant effect on financial management behavior. The advice that can be given from this research is to be able to develop good behavioral habits of financial management by providing funds for urgent needs, being able to control the finances owned and updating information about finance through various media.